Penerapan Media Koyong dalam Meningkatkan Hasil Belajar Siswa Materi Pentingnya Gotong Royong di Kelas 1 SD - Sitorus, Theresia Febiola; Mushlihuddin, Rahmat; Feviana, Lia (Lembaga Yasin AlSys, 2025)
This study is motivated by the characteristics of early grade students who tend to be energetic and physically active, often resulting in a less conducive classroom atmosphere. The aim of this research is to improve the learning outcomes of Class 1B students at SD Negeri 060913 Medan on the topic “The Importance of Gotong Royong” through the application of the innovative learning media Koyong (Kotak Gotong Royong). This study is a Classroom Action Research (PTK) using the Kemmis and Taggart model, conducted in two cycles during the even semester of the 2024/2025 academic year, involving 23 students as subjects. Data collection techniques included learning outcome tests and observations of student and teacher activities. The results show that prior to the intervention, only 61% of students achieved mastery learning, while after the implementation of the Koyong media in Cycle II, mastery increased to 87%. This improvement is attributed to the use of concrete, interactive, and enjoyable media, which enhanced students' motivation, engagement, and understanding of gotong royong (collective work practice) values. In conclusion, the Koyong media is effective in creating a conducive learning environment and improving student learning outcomes, while also fostering positive attitudes and social values from an early age. The implications of this study highlight the importance of using creative and contextual learning media by teachers to support character development in elementary education.